Socialization of Cervical Cancer Prevention Program in Panglanjan Hamlet, Cintaratu Village, Pangandaran - Udin Rosidin; Iceu Amira; Hendrawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Along with advances in technological advances, several public health problems have been discovered. These health problems include increasing morbidity and mortality rates in non-communicable diseases. Non-communicable diseases are the main cause of death worldwide, accounting for around 63% of all deaths. One of the groups of non-communicable diseases that causes death is cervical cancer. Cervical cancer is one of the most common cancers in Indonesia. Based on data from the cancer profile in Indonesia in 2020, there were 36,633 new cases of cervical cancer and 21,033 deaths. It is reported that around 16.9 per 100,000 women in Indonesia are diagnosed with cervical cancer every year. In Indonesia, cervical cancer is still a serious public health problem, especially in rural areas which often receive less attention in terms of access to information and health services. Seeing this phenomenon, socializing cervical cancer prevention programs is a very important effort to carry out. The aim of this outreach activity is to educate the public so that there is increased knowledge about the importance of early detection and efforts to prevent cervical cancer that can be carried out. The activity method is in the form of health education about preventing cervical cancer. There were 34 female participants aged between 21 and 54 years. The results of the activity showed that the average knowledge score before the activity was 47 points and after the health education was 62 points. The conclusion was that there was an increase in knowledge after health education was carried out by 15 points. It is hoped that the outreach activities for the cervical cancer prevention program that have been implemented can be continued periodically by the Selasari Health Center and Cintaratu Village, Parigi District, Pangandaran Regency.